Implementación de un sistema automático para riego y fertilización de zonas verdes en el área de recreación de la Universidad Técnica de Cotopaxi - Analuisa Taipe, Edgar Patricio (2016)
An automatic system for irrigation and fertilization spray, which allows exploit the water resources available at the Technical University of Cotopaxi efficient in the agronomic field, the lack of technology for this process, makes implemented that irrigation shifts is manually and with an involuntary waste of vital fluid, a field study was conducted and by observing a thorough investigation in the agronomic, hydraulic and electric field was developed, allowing a diagnosis for the given area and the amount of water was used, it was measured to compare the reduction of the vital liquid, in addition by a survey determine the strategic points to place sprinklers evenly, equally the electrical design is stressed, in order to automate the system in a way simple, practical and easy operation for the user, thereby sowing, knowledge that can be applied together to obtain a system of irrigation technology innovative and efficient, thereby increasing the amount of water is reduced and the time needed to implement it, and this way managed to control the vital liquid waste, according to the results determined to be feasible. And finally an operating manual was developed, so that the user can easily become familiar with the implemented system and can perform basic maintenance activities on it, via a practical guide.